Strengthening Pro-Environmental Behavior through Methane Gas Utilization and Environmental Education at Talangagung Landfill - Muhammad Zainush Sholihin; Hamamah Hamamah; Agung Pramana Warih Marhendra (AL-ISHLAH: Jurnal Pendidikan, 2026)
Despite growing attention to pro-environmental behavior, existing studies have largely examined environmental education and methane gas utilization separately, providing limited understanding of how their integration promotes sustainable behavioral change in landfill communities. This study investigates how environmental education integrated with methane gas utilization strengthens pro-environmental behavior among communities surrounding Talangagung Landfill, Indonesia. A qualitative case study was conducted at Talangagung Landfill involving 30 purposively selected participants, including local government officials, landfill managers, community members, and waste workers. Data were collected through semi-structured interviews, participant observation, and document analysis and analyzed using thematic analysis supported by data triangulation and member checking. Four interrelated dimensions emerged. First, environmental education enhanced environmental literacy, ecological responsibility, and long-term behavioral commitment. Second, methane gas utilization reduced household cooking fuel expenditure by IDR 50,000–100,000 per month while increasing participation in waste management activities. Third, community participation reinforced waste sorting, composting, waste bank engagement, and collective environmental maintenance through social learning. Fourth, institutional support strengthened program sustainability through infrastructure development, environmental regulations, and multi-stakeholder collaboration. However, unequal environmental literacy, infrastructure limitations, and inconsistent policy implementation remained significant challenges. The findings demonstrate that integrating environmental education with methane gas utilization creates complementary educational, economic, social, and institutional mechanisms that foster sustained pro-environmental behavior. The proposed Four-Pillar Model extends pro-environmental behavior theory by illustrating how economic incentives reinforce environmental learning and collective action, offering a transferable framework for community-based environmental education and sustainable landfill management.